Multi-band infrared absorption masterbatch and preparation method thereof

The multi-band infrared absorption masterbatch is prepared by a combination of carrier resin, KxWO3 and modified CsyWO3, which solves the problem of poor absorption effect of existing materials in the multi-band, achieves high absorption rate and long-term stability, and is suitable for infrared absorption and thermal insulation applications.

CN118931010BActive Publication Date: 2025-04-11GUANGDONG DICAI NEW MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411091579.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-09
Publication Date
2025-04-11
Estimated Expiration
2044-08-09

AI Technical Summary

Technical Problem

The existing infrared absorbing materials have poor absorption effects in multi-band and wideband, and nano-oxide powders are prone to agglomeration and unstable.

Method used

Using a combination of carrier resin, KxWO3 and modified CsyWO3, multi-band infrared absorption masterbatches are prepared by sonication and ball milling, and the microstructure and component ratio of the material are controlled to achieve high absorption rate and long-term stability.

Benefits of technology

It achieves high absorption rate in the multi-band infrared region, but basically no absorption in the visible region, and has excellent long-term stability, and is suitable for infrared absorption and thermal insulation applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004986730520000091
    Figure BDA0004986730520000091
  • Figure BDA0004986730520000101
    Figure BDA0004986730520000101
Patent Text Reader

Abstract

A multi-band infrared absorption masterbatch and a preparation method thereof, belonging to the field of infrared absorption technology. The infrared absorption masterbatch is characterized in that, based on the total mass percentage of 100%, it includes the following raw material components: 55-75% carrier resin, 10-15% K x WO3 and 15‑30% modified Cs y WO3; wherein 0<x<1, 0<y<1; the K x WO3 and the modified Cs y The mass ratio of WO3 is 1:1.5-2. The infrared absorption masterbatch of the present invention has a high absorption rate in the multi-band infrared region, and has almost no absorption in the visible region, and has excellent long-term stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of infrared absorption, and in particular relates to a multi-band infrared absorption masterbatch and a preparation method thereof. Background Art

[0002] Infrared is an invisible ray between visible light and microwaves, with a wavelength range of about 0.75-1000μm, and is divided into three parts: "near infrared", "mid infrared" and "far infrared". Infrared absorption materials refer to special functional materials that have strong absorption of a certain band or several bands of infrared light. It can be a single compound or a composite of two or more materials. Infrared absorption materials can be used to absorb the infrared radiation of the target to counter infrared reconnaissance, and can also shield the light source in the infrared light area from irradiation or prevent heat loss to play a role in heat insulation.

[0003] At present, the infrared absorption materials at home and abroad mainly include: silicon carbide, silicon nitride nanopowder, cobalt nickel nanofilm, nanographite, Fe, Co, Ni and other nanometals and alloys, nanometal oxides, nanoneedle-shaped magnetic metal powders, multilayer nanofilm composite absorbers, composite absorbers of chiral and nanomagnetic metal ions, iron nitride solid superparamagnetic composite absorbers, iron-based nanoneedle-shaped powders, etc. Among them, the unique structure of nanometal oxides gives them unique performance and advantages in infrared absorption materials, but nanooxide powders are easy to agglomerate and difficult to disperse evenly, and they are unstable and easy to age, and a single absorption material is difficult to achieve multi-band and broadband absorption effects.

[0004] Patent CN104559118B discloses a method for preparing a special masterbatch for PC sunlight panels by adding antimony tin oxide (ATO) nano-infrared functional particles. The disadvantage is that ATO has a good effect on blocking long-wave near-infrared rays (1500-2500nm), but has a poor effect on blocking short-wave near-infrared rays (780-1400nm) that are sensitive to human body heat. Summary of the invention

[0005] In view of the deficiencies in the prior art, an object of the present invention is to provide a multi-band infrared absorption masterbatch, which has a high absorptivity in the multi-band infrared region and substantially no absorption in the visible region, and has excellent long-term stability.

[0006] In order to achieve the above object, according to one aspect of the present invention, a multi-band infrared absorption masterbatch is provided, which comprises the following raw material components according to the total mass percentage of 100%: 55-75% carrier resin, 10-15% K x WO3 and 15-30% modified Cs y WO3; wherein 0<x<1, 0<y<1; the K x WO3 and the modified Csy The mass ratio of WO3 is 1:1.5-2.

[0007] In some embodiments, the K x The average length of WO3 is 150-300nm, the average diameter is 10-20nm, and the average aspect ratio is 13-15.

[0008] In some embodiments, the modified Cs y WO3 is Cs coated with polyvinyl pyrrolidone on the outside. y WO3; the modified Cs y In WO3, the mass proportion of polyvinyl pyrrolidone is 3-5%.

[0009] In some embodiments, the modified Cs y The particle size of WO3 is 140-160nm.

[0010] In some embodiments, the carrier resin includes any one or more of polyethylene, polypropylene, and polyester.

[0011] According to another aspect of the present invention, there is also provided a method for preparing the above-mentioned multi-band infrared absorption masterbatch, comprising the following steps:

[0012] (1) Preparation of K x WO3: Tungsten chloride and potassium acetate are added to ethanol in a molar ratio of 2:1, ultrasonicated and stirred until fully dissolved, reacted at 180-190°C for 20-24h, centrifuged and dried after the reaction, and the K x WO3;

[0013] (2) Preparation of modified Cs y WO3: Cs y WO3 is added to ethanol for ball milling, and an ethanol solution of polyvinyl pyrrolidone is added, stirred evenly, and ultrasonically treated. The dispersion after ultrasonic treatment is centrifuged and dried to obtain the modified Cs y WO3;

[0014] (3) The K x WO3, the modified Cs in step (2) y After WO3 and the carrier resin are uniformly mixed in proportion, they are sent to a twin-screw extruder for melt extrusion granulation and drying to obtain the multi-band infrared absorption masterbatch.

[0015] In some embodiments, in step (1), the concentration of tungsten chloride in ethanol is 13-15 mg / mL.

[0016] In some embodiments, in step (2), the Cs yThe mass ratio of WO3 to polyvinyl pyrrolidone is 100:6-10.

[0017] In some embodiments, in step (3), the rotation speed of the twin-screw extruder is 100-500 r / min, and the temperature of each screw zone of the twin-screw extruder is 180-230°C.

[0018] According to another aspect of the present invention, there is also provided application of the above-mentioned multi-band infrared absorption masterbatch or the multi-band infrared absorption masterbatch prepared according to the above-mentioned preparation method in a film.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) The present invention provides a multi-band infrared absorbing masterbatch by x WO3 and modified Cs y WO3 is mixed, and the optimal addition ratio of the two substances is further found. The two substances work synergistically to achieve maximum infrared absorption performance without sacrificing visible light transmittance, so that the masterbatch has high absorption rate in the multi-band infrared region and basically no absorption in the visible region, and has excellent long-term stability.

[0021] (2) The preparation method of the multi-band infrared absorption masterbatch of the present invention is simple and has good application prospects. DETAILED DESCRIPTION

[0022] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0023] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0024] Herein, when describing embodiments or examples, it should be understood that they are not used to limit the present invention to these embodiments or examples. On the contrary, all substitutes, improvements and equivalents of the methods and materials described in the present invention can be included in the scope limited by the claims.

[0025] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0026] The present invention provides a multi-band infrared absorption masterbatch, comprising the following raw material components: carrier resin, K x WO3 and modified Cs y WO3; wherein 0<x<1, 0<y<1. In some embodiments, x=0.3, y=0.33. In some embodiments, the K x WO3 and the modified Cs y The mass ratio of WO3 is 1:1.5-2. It is understandable that the mass ratio can be any specific value of 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2 or any value within the range of 1:1.5-2. The inventors of the present invention have found that by controlling the K x WO3 and the modified Cs y The mass ratio of WO3 can further regulate the comprehensive optical properties of the masterbatch, maximize the synergistic effect of the two substances, and achieve maximum infrared absorption performance without sacrificing visible light transmittance.

[0027] In the present invention, in the infrared absorbing masterbatch, the mass fraction of the carrier resin is 55-75% based on the total mass percentage of 100%. It can be understood that the mass fraction can be any specific value of 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, or any value within the range of 55-75%. In some embodiments, the carrier resin includes any one or more of polyethylene, polypropylene, and polyester.

[0028] In the present invention, in the infrared absorbing masterbatch, based on the total mass percentage of 100%, the K x The mass fraction of WO3 is 10-15%. It is understood that the mass fraction can be any specific value of 10%, 11%, 12%, 13%, 14%, 15%, or any value within the range of 10-15%. In some embodiments, the K x The average length of WO3 is 150-300nm, the average diameter is 10-20nm, and the average aspect ratio is 13-15. xWO3 can not only ensure its dispersion uniformity and stability in the masterbatch, but also ensure a higher carrier concentration, thereby improving the infrared absorption performance.

[0029] In the present invention, in the infrared absorbing masterbatch, based on the total mass percentage of 100%, the modified Cs y The mass fraction of WO3 is 15-30%. It is understood that the mass fraction can be any specific value of 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, or any value within the range of 15-30%. In some embodiments, the modified Cs y WO3 is Cs coated with polyvinyl pyrrolidone on the outside. y WO3; the modified Cs y In WO3, the mass proportion of polyvinyl pyrrolidone is 3-5%. In some embodiments, the modified Cs y The particle size of WO3 is 140-160nm. It can be understood that the particle size can be any specific value of 140nm, 142nm, 144nm, 146nm, 148nm, 150nm, 152nm, 154nm, 156nm, 158nm, 160nm or any value within the range of 140-160nm.

[0030] The inventors of the present invention have found that using a specific content of polyvinyl pyrrolidone to modify Cs y WO3, and further adjusted the modified Cs y The mass proportion of polyvinyl pyrrolidone in WO3 and the obtained modified Cs y WO3 can take into account both long-term dispersion stability and excellent infrared absorption performance. y The mass proportion of polyvinyl pyrrolidone in WO3 is relatively low, so the dispersion stability is not significantly improved; if the modified Cs y The mass proportion of polyvinyl pyrrolidone in WO3 is relatively high, the dispersion stability will be reduced, and the infrared absorption performance will also be significantly reduced.

[0031] According to another aspect of the present invention, there is also provided a method for preparing the above-mentioned multi-band infrared absorption masterbatch, comprising the following steps:

[0032] (1) Preparation of K x WO3: Tungsten chloride and potassium acetate are added to ethanol in a molar ratio of 2:1, ultrasonicated and stirred until fully dissolved, reacted at 180-190°C for 20-24h, centrifuged and dried after the reaction, and the K x WO3;

[0033] (2) Preparation of modified Cs y WO3: Cs y WO3 is added to ethanol for ball milling, and an ethanol solution of polyvinyl pyrrolidone is added, stirred evenly, and ultrasonically treated. The dispersion after ultrasonic treatment is centrifuged and dried to obtain the modified Cs y WO3;

[0034] (3) The K x WO3, the modified Cs in step (2) y After WO3 and the carrier resin are uniformly mixed in proportion, they are sent to a twin-screw extruder for melt extrusion granulation and drying to obtain the multi-band infrared absorption masterbatch.

[0035] In the present invention, in step (1), tungsten chloride and potassium acetate are added to ethanol in a molar ratio of 2:1, ultrasonicated and stirred until fully dissolved, reacted at 180-190°C for 20-24h, and centrifuged and dried after the reaction to obtain the K x WO3. In some embodiments, in step (1), the concentration of tungsten chloride in ethanol is 13-15 mg / mL. The present invention can effectively control the obtained K by controlling the concentration of tungsten chloride. x The microscopic size of WO3 ensures K x WO3 and modified Cs y Effective synergy of WO3.

[0036] In the present invention, in step (2), Cs y WO3 is added to ethanol for ball milling, and an ethanol solution of polyvinyl pyrrolidone is added, stirred evenly, and ultrasonically treated. The dispersion after ultrasonic treatment is centrifuged and dried to obtain the modified Cs y WO3. In some embodiments, the ball milling time may be 2-4 hours. In some embodiments, the stirring time may be 1-2 hours. In some embodiments, the ultrasonic treatment time may be 0.5-1 hour. In some embodiments, the Cs y The mass ratio of WO3 and polyvinyl pyrrolidone is 100:6-10. It is understood that the mass ratio can be any specific value of 100:6, 100:6.5, 100:7, 100:7.5, 100:8, 100:8.5, 100:9, 100:9.5, 100:10 or any value within the range of 100:6-10. In the present invention, by controlling the Cs y The mass ratio of WO3 and polyvinyl pyrrolidone can be adjusted to modify the Cs y The content of polyvinyl pyrrolidone in WO3 can further ensure good dispersion stability and infrared absorption. yThe mass ratio of WO3 and polyvinyl pyrrolidone is low, that is, the content of polyvinyl pyrrolidone is too high. y If the thickness of WO3 surface coating is too thick, the dispersion stability and infrared absorption performance will decrease. y The mass ratio of WO3 and polyvinyl pyrrolidone is too high, that is, the content of polyvinyl pyrrolidone is too low. y The thickness of WO3 surface coating is too thin, resulting in unclear modification effect.

[0037] In the present invention, in step (3), the K x WO3, the modified Cs in step (2) y After WO3 and the carrier resin are mixed uniformly in proportion, they are sent to a twin-screw extruder for melt extrusion granulation and drying to obtain the multi-band infrared absorption masterbatch. In some embodiments, in step (3), the rotation speed of the twin-screw extruder is 100-500r / min. It can be understood that the rotation speed can be any specific value of 100r / min, 150r / min, 200r / min, 250r / min, 300r / min, 350r / min, 400r / min, 450r / min, 500r / min or any value within the range of 100-500r / min. In some embodiments, the temperature of each zone of the screw of the twin-screw extruder is 180-230°C. It can be understood that the temperature can be any specific value of 180°C, 185°C, 190°C, 195°C, 200°C, 205°C, 210°C, 215°C, 220°C, 225°C, 230°C or any value within the range of 180-230°C.

[0038] According to another aspect of the present invention, there is also provided application of the above-mentioned multi-band infrared absorption masterbatch or the multi-band infrared absorption masterbatch prepared according to the above-mentioned preparation method in a film.

[0039] The present invention will be described in detail below by way of examples. It should be understood that the following examples are only used to further explain and illustrate the content of the present invention by way of example, and are not intended to limit the present invention.

[0040] Unless otherwise specified, the raw materials in the examples and comparative examples of the present invention are all commercially available, and the specific information is as follows:

[0041] Polyethylene resin: The melt mass flow rate MFR under the test conditions of 230°C and 2.16kg load is 12g / 10min, manufacturer: Qilu Petrochemical; Polypropylene resin: The melt mass flow rate MFR under the test conditions of 230°C and 2.16kg load is 16g / 10min, manufacturer: Qilu Petrochemical; Polyvinyl pyrrolidone: purchased from Beijing Bailingwei Technology Co., Ltd.; Tungsten chloride, potassium acetate, ethanol: purchased from Aladdin; Cs y WO3: 30-50nm, y=0.33, purchased from Zhejiang Zhiti Nano Micro New Materials Co., Ltd.

[0042] Example 1

[0043] The multi-band infrared absorption masterbatch described in this embodiment includes the following raw material components based on the total mass percentage of 100%: 70% polyethylene resin, 10% K x WO3 and 20% modified Cs y WO3; wherein x=0.3, y=0.33.

[0044] The method for preparing the multi-band infrared absorption masterbatch described in this embodiment comprises the following steps:

[0045] (1) Preparation of K x WO3: 8 g tungsten chloride and 0.1 g potassium acetate were added to 0.6 L ethanol, ultrasonicated and stirred until fully dissolved, reacted at 180 °C for 24 h, centrifuged after the reaction, and dried at 60 °C for 24 h to obtain the K x WO3;

[0046] (2) Preparation of modified Cs y WO3: 100gCs y WO3 was added to 80 mL of ethanol and ball-milled for 2 h, 10 mL of ethanol solution containing 10 g of polyvinyl pyrrolidone was added, stirred for 1 h until uniform, and ultrasonically treated for 1 h. The dispersion after ultrasonic treatment was centrifuged and dried at 60 ° C for 24 h to obtain the modified Cs y WO3;

[0047] (3) 5g of K x WO3, 10g modified Cs in step (2) y After WO3 and 35g polyethylene resin are evenly mixed, they are sent to a twin-screw extruder for melt extrusion granulation. The rotation speed of the twin-screw extruder is 500r / min, and the extrusion temperatures in the screws of the twin-screw extruder are: 180°C in zone one, 190°C in zone two, 195°C in zone three, 210°C in zone four, 220°C in zone five, and dried at 70°C to obtain the multi-band infrared absorption masterbatch.

[0048] Example 2

[0049] The multi-band infrared absorption masterbatch described in this embodiment includes the following raw material components based on the total mass percentage of 100%: 55% polypropylene resin, 15% K x WO3 and 30% modified Cs y WO3; wherein x=0.3, y=0.33.

[0050] The method for preparing the multi-band infrared absorption masterbatch described in this embodiment comprises the following steps:

[0051] (1) Preparation of K x WO3: 8 g tungsten chloride and 0.1 g potassium acetate were added to 0.55 L ethanol, ultrasonicated and stirred until fully dissolved, reacted at 190 °C for 20 h, centrifuged after the reaction, and dried at 60 °C for 24 h to obtain the K x WO3;

[0052] (2) Preparation of modified Cs y WO3: 100gCs y WO3 was added to 80 mL of ethanol and ball-milled for 2 h, 10 mL of ethanol solution containing 6 g of polyvinyl pyrrolidone was added, stirred for 1 h until uniform, and ultrasonically treated for 1 h. The dispersion after ultrasonic treatment was centrifuged and dried at 60 ° C for 24 h to obtain the modified Cs y WO3;

[0053] (3) 6g of K x WO3, 12g modified Cs in step (2) y After WO3 and 22g of polypropylene resin are evenly mixed, they are sent to a twin-screw extruder for melt extrusion granulation. The rotation speed of the twin-screw extruder is 100r / min, and the extrusion temperatures in the screws of the twin-screw extruder are: 180°C in zone one, 190°C in zone two, 195°C in zone three, 210°C in zone four, 220°C in zone five, and dried at 70°C to obtain the multi-band infrared absorption masterbatch.

[0054] Example 3

[0055] The multi-band infrared absorption masterbatch described in this embodiment includes the following raw material components based on the total mass percentage of 100%: 75% polyethylene resin, 10% K x WO3 and 15% modified Cs y WO3; wherein x=0.3, y=0.33.

[0056] The method for preparing the multi-band infrared absorption masterbatch described in this embodiment comprises the following steps:

[0057] (1) Preparation of K xWO3: 8 g tungsten chloride and 0.1 g potassium acetate were added to 0.6 L ethanol, ultrasonicated and stirred until fully dissolved, reacted at 185 °C for 24 h, centrifuged after the reaction, and dried at 60 °C for 20 h to obtain the K x WO3;

[0058] (2) Preparation of modified Cs y WO3: 100gCs y WO3 was added to 80 mL of ethanol and ball-milled for 2 h, 10 mL of ethanol solution containing 7.5 g of polyvinyl pyrrolidone was added, stirred for 1 h until uniform, and ultrasonically treated for 1 h. The dispersion after ultrasonic treatment was centrifuged and dried at 60 ° C for 20 h to obtain the modified Cs y WO3;

[0059] (3) 6g of K x WO3, 9g modified Cs in step (2) y After WO3 and 45g polyethylene resin are evenly mixed, they are sent to a twin-screw extruder for melt extrusion granulation. The rotation speed of the twin-screw extruder is 300r / min, and the extrusion temperatures in the screws of the twin-screw extruder are: 180°C in zone one, 190°C in zone two, 195°C in zone three, 210°C in zone four, 220°C in zone five, and dried at 70°C to obtain the multi-band infrared absorption masterbatch.

[0060] Comparative Example 1

[0061] The preparation method of the infrared absorbing masterbatch of this comparative example is the same as that of Example 1, except that the mass fraction of the polyethylene resin in the infrared absorbing masterbatch is 60%, K x The mass fraction of WO3 is 20%, and the modified Cs y The mass fraction of WO3 is 20%.

[0062] Comparative Example 2

[0063] The preparation method of the infrared absorbing masterbatch of this comparative example is the same as that of Example 1, except that the infrared absorbing masterbatch does not contain K x WO3. The specific composition and preparation method are as follows:

[0064] The infrared absorption masterbatch in this comparative example, based on the total mass percentage of 100%, includes the following raw material components: 70% polyethylene resin and 30% modified Cs y WO3; wherein y=0.33.

[0065] The preparation method of the infrared absorbing masterbatch described in this comparative example comprises the following steps:

[0066] (1) Preparation of modified Cs y WO3: and the modified Cs prepared in Example 1y The steps for WO3 are the same;

[0067] (2) 30 g of the modified Cs y After WO3 and 70g polyethylene resin are evenly mixed, they are sent to a twin-screw extruder for melt extrusion granulation. The rotation speed of the twin-screw extruder is 300r / min, and the extrusion temperatures in the screws of the twin-screw extruder are: 180°C in zone 1, 190°C in zone 2, 195°C in zone 3, 210°C in zone 4, 220°C in zone 5, and dried at 70°C to obtain the infrared absorbing masterbatch.

[0068] Comparative Example 3

[0069] The preparation method of the infrared absorbing masterbatch of this comparative example is the same as that of Example 1, except that K x WO3 and modified Cs y The mass ratio of WO3 is 1:1. The specific composition and preparation method are as follows:

[0070] The infrared absorption masterbatch in this comparative example, based on the total mass percentage of 100%, includes the following raw material components: 70% polyethylene resin, 15% K x WO3, 15% modified Cs y WO3; wherein x=0.3, y=0.33.

[0071] The preparation method of the infrared absorbing masterbatch described in this comparative example comprises the following steps:

[0072] (1) Preparation of K x WO3: same as step (1) of Example 1;

[0073] (2) Preparation of modified Cs y WO3: same as step (2) of Example 1;

[0074] (3) 3g of K in step (1) x WO3, 3g modified Cs in step (2) y After WO3 and 14g polyethylene resin are evenly mixed, they are sent to a twin-screw extruder for melt extrusion granulation. The rotation speed of the twin-screw extruder is 500r / min, and the extrusion temperatures in the screws of the twin-screw extruder are: 180°C in zone 1, 190°C in zone 2, 195°C in zone 3, 210°C in zone 4, 220°C in zone 5, and dried at 70°C to obtain the infrared absorbing masterbatch.

[0075] Performance Testing

[0076] The modified Cs obtained in Examples 1-3 of the present invention y WO3 was characterized according to the following test method, and the specific characterization data are shown in Table 1.

[0077] Modified Cs y Mass proportion of polyvinyl pyrrolidone in WO3: The modified Cs y Thermal gravimetric curve of WO3 particles, calculation of modified Cs by mass loss y Mass proportion of polyvinyl pyrrolidone in WO3.

[0078] Particle size: Zetasizer 3000 laser particle size analyzer was used to analyze the modified Cs y The particle size of WO3 particles.

[0079] Table 1 Modified Cs in Examples 1-3 y Characterization data of WO3

[0080]

[0081] K obtained in Examples 1-3 of the present invention x WO3 was characterized according to the following test method, and the specific characterization data are shown in Table 2.

[0082] Size: 50 K were measured using transmission electron microscopy x The length and diameter of WO3 particles are calculated from the measured length and diameter. In addition, the K x The aspect ratio (length / diameter) of WO3 particles was then calculated and the average aspect ratio was obtained.

[0083] Table 2 K in Examples 1-3 x Characterization data of WO3

[0084] Example 1 Example 2 Example 3 Average length, nm 160 260 210 Average diameter, nm 12 18 15 Average aspect ratio 13.3 14.5 14.0

[0085] The infrared absorbing masterbatch described in Examples 1-3 of the present invention and Comparative Examples 1-3 was mixed with polyethylene resin pellets and melt co-extruded to obtain a plastic film, the mass fraction of the polyolefin masterbatch was 35%, and the thickness of the plastic film was 15 μm. The performance test was carried out according to the following test method, and the specific performance indicators are shown in Table 3.

[0086] Visible light transmittance and infrared absorptivity: Determined in accordance with GB / T2410-2008. Test the performance of the film after 0d and 30d of storage respectively. The visible light transmittance detection band is 380-780nm, and the infrared absorptivity detection band is 780-2500nm.

[0087] Table 3 Performance test data of films prepared from infrared absorbing masterbatch of Examples 1-3 and Comparative Examples 1-3

[0088]

[0089] As shown in Table 3, the films made of the infrared absorption masterbatch of Examples 1-3 of the present invention have high visible light transmittance and infrared absorption rate; at the same time, after being placed for 30 days, the visible light transmittance and infrared absorption rate still remain at a high level, indicating that the infrared absorption masterbatch of the present invention has good stability. x The content of WO3 is too high, and the initial visible light transmittance and infrared absorptivity of the obtained film are equivalent to those of Example 1; after 20 days of storage, its visible light transmittance and infrared absorptivity are greatly reduced, indicating that the excessive K x WO3 precipitates from the film, thus seriously affecting the optical properties; it can be seen from Example 1 and Comparative Example 2 that the infrared absorbing masterbatch in Comparative Example 2 does not contain K x WO3, the visible light transmittance of the obtained film is significantly reduced. It can be seen from Example 1 and Comparative Example 3 that the infrared light absorbing masterbatch in Comparative Example 3 contains K x WO3 and modified Cs y The mass ratio of WO3 is too high. After the obtained film is placed for 20 days, its visible light transmittance and infrared absorption rate are greatly reduced, indicating that K in the infrared light absorption masterbatch x WO3 and modified Cs y The content of WO3 has a great influence on the performance of the final film. An inappropriate content or mass ratio of the two will affect the dispersion stability of the particles, and thus affect the optical properties of the film.

[0090] In summary, the present invention can be seen by x WO3 and modified Cs y WO3 is mixed, and the optimal addition ratio of the two substances is further found. The two substances work synergistically to achieve maximum infrared absorption performance without sacrificing visible light transmittance, so that the masterbatch has high absorption rate in the multi-band infrared region and basically no absorption in the visible region, and has excellent long-term stability.

[0091] Obviously, the above embodiments of the present invention are only examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made on the basis of the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. A multi-band infrared absorption masterbatch, characterized in that: According to the total mass percentage of 100%, the raw material components include: 55-75% carrier resin, 10-15% K x WO3 and 15-30% modified Cs y WO3; Wherein, 0<x<1, 0<y<1; x WO3 and the modified Cs y The mass ratio of WO3 is 1:1.5-2; The modified Cs y WO3 is Cs coated with polyvinyl pyrrolidone y WO3; the modified Cs y In WO3, the mass proportion of polyvinyl pyrrolidone is 3-5%; The preparation method of the multi-band infrared absorption masterbatch comprises the following steps: (1) Preparation of K x WO3: Tungsten chloride and potassium acetate are added to ethanol in a molar ratio of 2:1, ultrasonicated and stirred until fully dissolved, reacted at 180-190°C for 20-24h, centrifuged and dried after the reaction, and the K x WO3; (2) Preparation of modified Cs y WO3: Cs y WO3 is added to ethanol for ball milling, and an ethanol solution of polyvinyl pyrrolidone is added, stirred evenly, and ultrasonically treated. The dispersion after ultrasonic treatment is centrifuged and dried to obtain the modified Cs y WO3; (3) Replace the K in step (1) x WO3, the modified Cs in step (2) y After WO3 and the carrier resin are uniformly mixed in proportion, they are sent to a twin-screw extruder for melt extrusion granulation and drying to obtain the multi-band infrared absorption masterbatch; In step (1), the concentration of tungsten chloride in ethanol is 13-15 mg / mL; In step (2), the Cs y The mass ratio of WO3 to polyvinyl pyrrolidone is 100:6-10.

2. The multi-band infrared absorption masterbatch according to claim 1, characterized in that: The K x The average length of WO3 is 150-300nm, the average diameter is 10-20nm, and the average aspect ratio is 13-15.

3. The multi-band infrared absorption masterbatch according to claim 1, characterized in that: The modified Cs y The particle size of WO3 is 140-160nm.

4. The multi-band infrared absorption masterbatch according to claim 1, characterized in that: The carrier resin includes any one or more of polyethylene, polypropylene, and polyester.

5. The method for preparing the multi-band infrared absorption masterbatch according to claim 1, characterized in that: In step (3), the rotation speed of the twin-screw extruder is 100-500 r / min, and the temperature of each screw zone of the twin-screw extruder is 180-230°C.

6. Use of the multi-band infrared absorption masterbatch according to any one of claims 1 to 5 in a film.

Citation Information

Patent Citations

  • Polycarbonate masterbatch capable of blocking ultraviolet rays and near infrared rays, preparation method and use thereof

    CN104559118B

  • Hexagonal crystal tungsten bronze short rod nanoparticles and preparation method thereof

    CN105502503A

  • Composite material for shielding of near infrared light and air cleaning, and preparation method thereof

    CN106362731A